(untitled) (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2022)
This study aims to determine the effect of the marketing mix, namely product, price, location, and promotion, on customer decisions to choose Simasker savings products PT. Kerinci People’s Development Bank. In this study using quantitative methods by processing primary data through questionnaires given to customers of Bank Kerinci as many as 50 respondents with Non Probability Sampling technique. The analysis used in this research includes instrument test, statistical test, classical assumption test, and multiple linear test. Based on the results of research tests conducted, namely: 1) Product variable (X1) has a positive and significant effect on Customer Decisions (Y); 2) Price variable (X2) has no effect on customer decisions (Y); 3) Location variable (X3) has no effect on customer decisions; 4) Promotion variable (X4) has a positive and significant effect on customer decisions.